COMPARISON OF DESARDA METHOD VERSUS LICHTENSTEIN METHOD FOR THE MANAGEMENT OF INGUINAL HERNIA: A SHORT-TERM OUTCOME ANALYSIS - SARASWAT, ANURAG; TAUHEED, FAHAD; GUPTA, PURSHOTAM DASS; VIKRAM SINGH, RAGHAVENDRA; BHATNAGAR, ASHOK (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Lichtenstein method is a gold standard surgery modality for the management of inguinal hernia but it is associated with post-operative complications such as groin pain, abdominal wall thickness, and surgical site infections. Desarda method is a physiologic non-mesh repair with no anticipated mesh related complications. The present prospective randomized study was conducted to compare short term outcomes of Desarda with Lichtenstein technique for the management of inguinal hernia. Methods: This was a prospective randomized study conducted on 60 patients undergoing surgery for inguinal hernia. The patients were allocated into two groups as follows, Group A (n=30) patients undergoing Desarda’s repair for inguinal hernia and Group B (n=30) patients undergoing Lichtenstein’s repair. The following outcome was measured, post-operative pain (Day 1, Day 3, Day 5) – visual analog scale, duration of hospital stay and complications. p value <0.05 was considered significant. Results: The demographics characteristic were similar in both the groups and not significant. The hospital stay duration was lower in Desarda group as compared to Lichtenstein groups and was significant (4.07±0.83 vs. 6.87±1.87 days). The post-operative VAS score at day 1, 3, and 5 were significantly lower in Desarda group as compared to Lichtenstein group. The incidence of complications were lesser in Desarda group as compared to Lichtenstein group but not significant. Conclusion: The Desarda technique was superior when compared to Lichtenstein method in terms of early recovery, post-operative pain, and complications for the management of inguinal hernia.